THE CORRELATION BETWEEN STUDENTS’ GRAMMAR MASTERY AND WRITING ACHIEVEMENTS OF ELEVENTH GRADE STUDENTS AT SMA NEGERI 5 PEMATANG SIANTAR - Lustriyani Petronella Sidabalok; Dumaris E. Silalahi; Herman Herman (Sean Institute, 2023)
The research is aimed to find out the correlation between students’ grammar mastery and writing achievement at SMA Negeri 5 Pematang Siantar. The grammar test is multiple choices (past tense), and the writing test is writing recount text. This research is the quantitative non-experimental research with the correlational research design. The population is the grade XI of SMA Negeri 5 Pematang Siantar with the total of 360 students. The sample is only one class (XI Science3). There are 36 students determined using the purposive sampling technique. Grammar mastery is the independent variable and writing achievement is the dependent variable. The technique of analysis data in this research calculating correlation coefficient using pearson product moment formula technique through manual with formula rxy. The result of this research showed an average of students’grammar mastery value is 67.44 and average of writing recount text is 66.88. On the calculating correlation coefficient, this research has a very strong correlation. Interpretation correlation is between 0.80-1.00. Because the correlation coefficient is 0,976 and the rtable in the degree of significances 1% (0,262). rxy= 0,976. T table 2,034 > t count= 0.262. It means that the null hypothesis (H0) is rejected and automatically the alternative hypothesis (H1) is accepted. It can be conclude that there is significant correlation between students’ grammar mastery and their achievement in writing recount text at second grade of Science3 at SMA Negeri 5 pematang Siantar. The data showed this research has a positive correlation. Because students has low score in grammar also has a bad score in writing recount text and the contrary.